On the Growth of Groups and Automorphisms. - Bridson, M (2005)
We consider the growth functions beta(Gamma)(n) of amalgamated free products Gamma = A *(C) B, where A congruent to B are finitely generated, C is free abelian and \A/C\ = A/B\ = 2. For every d is an element of N there exist examples with beta(Gamma)(n) similar or equal to n(d+1)beta(A)(n). There also exist examples with beta(Gamma)(n) similar or equal to e(n). Similar behavior is exhibited among Dehn functions.